Surgical Outcomes of Postural Instability in Patients With Cervical Myelopathy. Issue 10 (December 2020) - Yano, Toma; Fujishiro, Takashi; Obo, Takuya; Mori, Katsunori; Hayama, Sachio; Nakaya, Yoshiharu; Nakano, Atsushi; Baba, Ichiro; Neo, Masashi
Abstract : Study Design: This is a retrospective study. Objective: The objective of this study was to investigate the surgical outcomes of postural instability and its predictors in patients with cervical myelopathy (CM). Summary of Background Data: Although several studies have shown impaired postural stability in CM patients, there remains a paucity of literature examining its surgical outcome. Materials and Methods: Postural stability was assessed using a stabilometer preoperatively, at the early phase (3–6 months postoperatively), and 1-year postoperatively, employing 2 stabilometric parameters: sway area [SwA (cm 2 ): the amount of sway of gravity center assessed by the outer peripheral area of the stabilogram] and sway density [SwD (/cm): the indicator of proprioceptive reflexes calculated by the locus length of the stabilogram per SwA]. Twenty-seven healthy age-matched, sex-matched, and body mass index-matched subjects were recruited as controls. To investigate the predictors of postoperative postural instability, univariate, and multivariate analyses were performed, including demographic data, preoperative neurological symptom severity, radiographic findings, and preoperative stabilometric parameters as independent variables. Results: Altogether, 54 CM patients were included in the present study. SwA was 7.89±0.84, 4.78±0.68, and 4.85±0.49, and SwD was 14.63±0.85, 20.41±1.23, and 19.36±1.40 preoperatively, at the early phase, and 1-year postoperatively, respectively, and significant improvement was found in both parameters postoperatively. However, at all timepoints, these parameters were significantly worse in CM patients than in the healthy subjects (SwA: 2.68±0.24, SwD: 24.91±1.83). Multivariate analyses showed that worse preoperative stabilometric parameters were significantly related to worse postoperative stabilometric parameters. Conclusions: Surgery significantly improved postural stability in CM patients; however, it did not reach the level observed in healthy controls, even postoperatively. A predictor of greater residual postoperative postural instability was a greater level of preoperative postural instability. In CM patients, to achieve better surgical outcome of postural stability, surgical intervention is recommended before the symptoms related to bodily imbalance deteriorate. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.